2002
DOI: 10.1126/science.1066434
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Effect on Cloud Droplet Size Monitored from Satellite

Abstract: Aerosol concentration and cloud droplet radii derived from space-borne measurements are used to explore the effect of aerosols on cloud microphysics. Cloud droplet size is found to be largest (14 micrometers) over remote tropical oceans and smallest (6 micrometers) over highly polluted continental areas. Small droplets are also present in clouds downwind of continents. By using estimates of droplet radii coupled with aerosol load, a statistical mean relationship is derived. The cloud droplet size appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
345
4
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(370 citation statements)
references
References 24 publications
17
345
4
4
Order By: Relevance
“…In the recent years several set of satellite data have fostered a comprehensive description of the temporal and spatial variability of different aerosol species, from anthropogenic aerosols ) to desert dust (Léon and Legrand, 2003). The monitoring of aerosols from space has also been widely used during this last decade for the evaluation of aerosol influence on global climate change through the impact on the Earth-atmosphere radiation budget (Boucher and Tanré, 2000;Bréon et al, 2002). Primary aerosol quantity derived from space borne remote sensors operating in the solar spectrum is the aerosol optical thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years several set of satellite data have fostered a comprehensive description of the temporal and spatial variability of different aerosol species, from anthropogenic aerosols ) to desert dust (Léon and Legrand, 2003). The monitoring of aerosols from space has also been widely used during this last decade for the evaluation of aerosol influence on global climate change through the impact on the Earth-atmosphere radiation budget (Boucher and Tanré, 2000;Bréon et al, 2002). Primary aerosol quantity derived from space borne remote sensors operating in the solar spectrum is the aerosol optical thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, special attention has been dedicated to cloud interactions with desert aerosol particles [Rosenfeld et al, 2001;Bréon et al, 2002;DeMott et al, 2003;Kawamoto and Nakajima, 2003;Huang et al, 2006]. Measurements of the complex refractive index of atmospheric dust aerosols in central Asia [Sokolik et al, 1993] suggested that significant absorption of solar radiation could exist due to the considerable range of values for the imaginary part of the refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…For low, warm clouds, these changes will tend to add an additional net cooling to the climate system. Both satellite and in-situ observations have been used to determine the first indirect effect (Nakajima et al, 2001;Bréon et al, 2002;Feingold et al, 2003;Penner et al, 2004;Kaufmann et al, 2005). But it has been difficult to determine the 2nd indirect effect, because changes in the observed liquid water path, cloud height and cloud cover are influenced by large-scale and cloud-scale dynamics and thermodynamics as well as by the influence of aerosols on cloud microphysics.…”
Section: Introductionmentioning
confidence: 99%